Potential Immunotherapeutic Targets on Myeloid Cells for Neurovascular Repair After Ischemic Stroke - Zhu, Ziyu; Zheng, Li; Li, Yan; Huang, Tingting; Chao, Yu-Chieh; Pan, Lijun; Zhu, Hui; Zhao, Yanhua; Yu, Weifeng; Li, Peiying (Frontiers in Neuroscience, 2019)
Neurological deficits and cognitive dysfunctions caused by acute ischemic stroke pose enormous burden to the stroke families and the communities. Restoration of the normal function of the neurovascular unit following ischemic stroke is critical for improving neurological recovery and cognitive functions after stroke. Recent evidences suggest that the myeloid cells including both the resident microglia and infiltrating monocytes/macrophages and neutrophils are highly plastic in response to the environmental cues. They intimately interact with multiple components of the neurovascular unit in response to the alarmins, danger associated pattern molecules (DAMPs) and other signals released from the ischemic brain. The aim of this review is to discuss the reciprocal interactions between the myeloid cells and the ischemic neurovascular unit during the late repair phase of cerebral ischemic stroke. We also summarize potential immunotherapeutic targets on myeloid cells and new therapeutic approaches targeting myeloid cells, such as cell transplantation, mitochondrial dynamic and extracellular vesicles-based therapy and et al to enhance neurovascular repair for better stroke recovery.